1998
DOI: 10.1590/s1020-49891998000200001
|View full text |Cite
|
Sign up to set email alerts
|

Anticipating rotavirus vaccines: review of epidemiologic studies of rotavirus diarrhea in Argentina

Abstract: Rotavirus is the most common cause of severe diarrhea in children worldwide, and vaccines currently being field-tested could be available for childhood immunization in several years

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 16 publications
3
10
0
2
Order By: Relevance
“…The rate of healthcare utilization for rotavirus disease we found in Santa Rosa is similar to that found for other Latin American countries, and also remarkably consistent with global estimates derived by other studies (Gomez et al. 1998; Guardado et al.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The rate of healthcare utilization for rotavirus disease we found in Santa Rosa is similar to that found for other Latin American countries, and also remarkably consistent with global estimates derived by other studies (Gomez et al. 1998; Guardado et al.…”
Section: Discussionsupporting
confidence: 91%
“…The rate of healthcare utilization for rotavirus disease we found in Santa Rosa is similar to that found for other Latin American countries, and also remarkably consistent with global estimates derived by other studies (Gomez et al 1998;Guardado et al 2004;Parashar et al 2003). The proportion of diarrhoeal hospitalizations attributable to rotavirus is also consistent with other studies completed in the Americas and with estimates for other low-middleincome countries (Kane et al 2004;Parashar et al 2006).…”
Section: Discussionsupporting
confidence: 91%
“…The risk of requiring a medical visit to the hospital found in this study is similar to those found in Argentina, 4,11 Chile, 4 Peru 12 and the United States. 13 Nevertheless the risk of being hospitalized for rotavirus in Venezuela is higher than in Finland, 14 England and Wales, 15 Argentina, 4 Chile 4 and the United States 16 but lower than in Peru.…”
Section: Discussionsupporting
confidence: 83%
“…2 and Fisher exact tests (2 tailed) were used for statistical analysis. (11,988) of the 13,816 patients with diarrhea were fully evaluated for clinical and laboratory diagnosis. These patients were more likely to be male (57%) than female (43%; 6795 versus 5193; P ϭ 0.0038) and of low and marginal social class (84%).…”
Section: Methodsmentioning
confidence: 99%
“…We calculated mean outpatient and hospital unit costs for each region by taking a population-weighted mean of country-specific cost estimates. We estimated the mean length of hospital stay as 4 days [6,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], and diagnostic and medication costs were estimated as a proportion of the per visit and per diem costs [73,74]. Cost estimates were converted from year 2000 international dollars to 2007 US dollars with use of the Consumer Price Index [75], purchasing power parity, and official exchange rates [76].…”
Section: Health Care Costs Of Rotavirusmentioning
confidence: 99%